Gender and age differences in social anxiety among Iranian immigrants children in Kuala Lumpur Malaysia - Hashempour, Sara; Mansor, Mariani; Juhari, Rumaya; Arshat, Zarinah; Saidu, Mohammed Bashir (Invention Journals, 2017)
Studies from clinical populations about the children have shown that social anxiety is a disorder in early childhood to mid-adulthood. In this regard, this study focused on comparing the gender and age categories difference in social anxiety among Iranian primary school children living in Kuala Lumpur Malaysia. The sample size of this study is 215 primary school pupils aged between 9 – 12 years old; and data was collected using Social Anxiety Scale for Children – Revised (SASC-R) (La Greca & Stone, 1993). The result indicted no significant difference between male and female as well as age categories in social anxiety among the respondents. This means, children who participated in this study did not differ significant in terms of social anxiety disorder based on gender and age categories. By implication, early detection of social anxiety disorder among children would ease treatment and intervention which will subsequently prevent social anxiety.